Порівняльний аналіз показників енергетичної ефективності виробництва біодизельного палива з насіння ріпаку - Kovalko O.M.; Evtukhova T.O.; Chuprina L.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
The paper presents comparative analysis of the different approaches to the definition of energy-economy efficiency of biodiesel fuel from rape corn, and a conclusion is made regarding practicability of its production. Several prospective techniques of such conclusion justification are considered, including by the means of distribution of the full primary energy to renewable and non-renewable components, and to the energy of a traditional fuel and the energy of a primary raw material (rape), which are radically opposite from the point of view of their accessibility and economy practicability.